Descriptions of four species of grenadier fishes of the genera Hymenocephalus and Hymenogadus (Teleostei, Gadiformes, Macrouridae) from the New Zealand region and Tasman Sea, including two new species of Hymenocephalus - Mcmillan, Peter; Iwamoto, Tomio (Zootaxa, 2014)
Two new species of Hymenocephalus are described from the New Zealand region and Tasman Sea. Hymenocephalus fuscus sp. n. has 11–12 pelvic fin rays, is darkly pigmented, with enlarged bony ridges on the dorsal aspects of head, lacks a chin barbel, has few (16–19) gill rakers on inner side of first arch and is similar to other species in the H. aterrimus species group. Hymenocephalus maculicaudus sp. n. has 8 pelvic fin rays, a mid-lateral line of melanophores on body and tail that extends about a head length posterior to anal fin origin, a short (7–16 % HL) chin barbel and is similar to other species in the H. megalops species group. Hymenocephalus nascens has 12–14 pelvic fin rays, lacks a chin barbel, has a mid-lateral stripe of silvery (fresh) or brownish (preserved) pigment running along trunk and tail. Hymenogadus gracilis has a serrated (weak, near tip) first dorsal fin spine, 7–9 pelvic fin rays, long (20–30% HL) chin barbel, and one row of enlarged melanophores along lateral mid-line of the tail. Hymenocephalus nascens and Hymenogadus gracilis are recorded for the first time from the New Zealand region. A key to the known New Zealand species of Hymenocephalus and Hymenogadus is provided.